RBM20 Regulates Circular RNA Production From the Titin Gene. Issue 9 (14th October 2016) - Khan, Mohsin A.F.; Reckman, Yolan J.; Aufiero, Simona; van den Hoogenhof, Maarten M.G.; van der Made, Ingeborg; Beqqali, Abdelaziz; Koolbergen, Dave R.; Rasmussen, Torsten B.; van der Velden, Jolanda; Creemers, Esther E.; Pinto, Yigal M.
Abstract : Rationale: : RNA-binding motif protein 20 (RBM20) is essential for normal splicing of many cardiac genes, and loss of RBM20 causes dilated cardiomyopathy. Given its role in splicing, we hypothesized an important role for RBM20 in forming circular RNAs (circRNAs), a novel class of noncoding RNA molecules. Objective: : To establish the role of RBM20 in the formation of circRNAs in the heart. Methods and Results: : Here, we performed circRNA profiling on ribosomal depleted RNA from human hearts and identified the expression of thousands of circRNAs, with some of them regulated in disease. Interestingly, we identified 80 circRNAs to be expressed from the titin gene, a gene that is known to undergo highly complex alternative splicing. We show that some of these circRNAs are dynamically regulated in dilated cardiomyopathy but not in hypertrophic cardiomyopathy. We generated RBM20-null mice and show that they completely lack these titin circRNAs. In addition, in a cardiac sample from an RBM20 mutation carrier, titin circRNA production was severely altered. Interestingly, the loss of RBM20 caused only a specific subset of titin circRNAs to be lost. These circRNAs originated from the RBM20-regulated I-band region of the titin transcript. Conclusions: : We show that RBM20 is crucial for the formation of a subset of circRNAs that originate from the I-band of the titin gene. We propose that RBM20, by excluding specific exons from the pre-mRNA, provides the substrate to form this class of RBM20-dependent circRNAs. Abstract : Supplemental Digital Content is available in the text.